Optimizing gas well deliquification: Experimental analysis of surfactant-based strategies for liquid unloading in gas wells for enhanced recovery - Najeeb Anjum Soomro; Ubedullah Ansari; Bilal Shams; Muhammad Khan Memon; Darya Khan Bhutto; Zhang Rui; Yi Pan (Unconventional Resources)
This research examines the potential of surfactants, concentrating on the challenge of production decline caused by liquid accumulation in gas wells, while exploring the dynamics of liquid-filled gas wells. The main objective is to elucidate the complexities associated with liquid accumulation in gas wells through the application of sodium dodecyl sulfate (SDS) as an effective surfactant. SDS was identified as an appropriate option following comprehensive testing and analysis, showcasing notable efficacy in reducing surface tension and facilitating the separation of entrapped liquid from the surface. The investigation further examines carrier fluids, examining their potential to enhance the effectiveness of surfactants. Research indicates that condensate serves as a highly effective carrier fluid, owing to its compatibility with SDS and its inherent ability to mitigate foaming. This mixture guarantees the surfactant's ideal dispersion and interaction with the collected liquid, which enhances the unloading procedure.This approach enabled research to assess the merits and demerits of each technique. These evaluations provide critical insights to their respective benefits and challenges. Results demonstrated that high in a API gas well condensate, due to its non-foaming nature and high compatibility with SDS, serves as an optimal carrier fluid, ensuring uniform dispersion without compromising foam performance. The results of this research enhance one's understanding of the complex interactions of surfactants, carrier fluid, and injection techniques.This research provides valuable insights for field applications, offering an optimized surfactant-based approach to gas well deliquification. The findings also contribute to enhanced oil and gas recovery by prolonging well lifespan, reducing operational costs, and improving production efficiency. This work serves as a foundation for future studies in surfactant-based well unloading strategies, paving the way for improved reservoir management and sustained hydrocarbon production.